2016
DOI: 10.1161/atvbaha.116.307157
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Acetylcholine Receptor Relieves Angiotensin II–Induced Senescence in Vascular Smooth Muscle Cells by Raising Nicotinamide Adenine Dinucleotide–Dependent SIRT1 Activity

Abstract: Objective-α7 nicotinic acetylcholine receptor (α7nAChR) is a subtype of nAChR and has been reported to be involved in hypertension end-organ damage.In this study, we tested the role of α7nAChR in angiotensin II (Ang II)-induced senescence of vascular smooth muscle cells (VSMCs). Approach and Results-Expression of α7nAChR was not influenced by Ang II. Ang II induced remarkable senescent phenotypes in rodent and human VSMCs, including increased senescence-associated β-galactosidase activity, phosphorylation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
(60 reference statements)
3
38
0
1
Order By: Relevance
“…A study by Li, et al tested the role of α7nAChR in Ang II–induced senescence of VSMCs and found that activation of α7nAChR alleviates Ang II–induced VSMC senescence through promoting NAD + –SIRT1 pathway, suggesting that α7nAChR may be a potential therapeutic target for the treatment of Ang II–associated vascular aging disorders. 71 Interestingly, another ATVB publication by Gardner, et al suggested that senescent VSMCs may be active participants in CVD processes and assume a pro-inflammatory state and secrete factors that promote chemotaxis of mononuclear cells in vitro and in vivo and that release active MMP-9, secrete less collagen, and prime endothelial cells and VSMCs to a pro-inflammatory state. 72 And while this was established in a model of atherosclerosis, whether this VSMC phenotype plays a direct role in arterial stiffness remains to be investigated.…”
Section: Underlying Mechanisms Of Arterial Stiffeningmentioning
confidence: 99%
“…A study by Li, et al tested the role of α7nAChR in Ang II–induced senescence of VSMCs and found that activation of α7nAChR alleviates Ang II–induced VSMC senescence through promoting NAD + –SIRT1 pathway, suggesting that α7nAChR may be a potential therapeutic target for the treatment of Ang II–associated vascular aging disorders. 71 Interestingly, another ATVB publication by Gardner, et al suggested that senescent VSMCs may be active participants in CVD processes and assume a pro-inflammatory state and secrete factors that promote chemotaxis of mononuclear cells in vitro and in vivo and that release active MMP-9, secrete less collagen, and prime endothelial cells and VSMCs to a pro-inflammatory state. 72 And while this was established in a model of atherosclerosis, whether this VSMC phenotype plays a direct role in arterial stiffness remains to be investigated.…”
Section: Underlying Mechanisms Of Arterial Stiffeningmentioning
confidence: 99%
“…Nicotine might lead to suppressed apoptosis and cisplatin resistance via α5nAChR/AKT signaling [112]. In addition, α7nAChR may be implicated in the NAD + /SIRT1 pathway, which promotes chemotherapeutic drug resistance [131]. Nicotine/α9nAChR signaling can reduce apoptotic pathways [116].…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT1-PARP-1 axis plays a critical role in the regulation of cigarette smoke-induced autophagy and has notable implications for understanding the mechanisms of cigarette smoke-induced cell death and senescence [130]. α7nAChR-SIRT1 axis activation alleviates angiotensin II-induced VSMC senescence [131]. Recent studies have focused on the biological functions of SIRT1 in metabolic diseases, cancer, aging and cellular senescence, inflammatory signaling in response to environmental stress, and cell survival [132][133][134][135].…”
Section: Sirt1mentioning
confidence: 99%
“…Ang II stimulation also induces senescence of vascular cells (Li et al, 2016;Kunieda et al, 2006). Moreover, Ang II is a potent mediator of oxidative stress and oxidant signaling leading to vascular premature senescence (Andrés, 2014).…”
Section: Discussionmentioning
confidence: 99%